4/x+2=5/2x+1 giúp mình với ạ!
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(x-\dfrac{3}{2}\right)\times\left(2x+1\right)>0\)
Th1:
\(x-\dfrac{3}{2}>0\Leftrightarrow x>\dfrac{3}{2}\)
\(2x+1>0\Leftrightarrow2x>1\Leftrightarrow x>\dfrac{1}{2}\)
( 1 )
Th2:
\(x-\dfrac{3}{2}< 0\Leftrightarrow x< \dfrac{3}{2}\)
\(2x+1< 0\Leftrightarrow2x< -1\Leftrightarrow x< -\dfrac{1}{2}\)
( 2 )
Từ ( 1 ) và ( 2 ), ta có:
\(\Rightarrow x< -\dfrac{1}{2};x>\dfrac{3}{2}\)
\(\left(2-x\right)\times\left(\dfrac{4}{5}-x\right)< 0\)
Th1:
\(2-x>0\Leftrightarrow x>2\)
\(\dfrac{4}{5}-x< 0\Leftrightarrow x< \dfrac{4}{5}\)
( Loại )
Th2:
\(2-x< 0\Leftrightarrow x< 2\)
\(\dfrac{4}{5}-x>0\Leftrightarrow x>\dfrac{4}{5}\)
=> \(\dfrac{4}{5}< x< 2\)
\(\Leftrightarrow6x-3-4x+20< =4x-1+24\)
=>2x+17-4x-23<=0
=>-2x-6<=0
=>-2x<=6
hay x>=-3
\(\Leftrightarrow\dfrac{6x-3-4x+20-4x+1-24}{12}\le0\)
\(\Rightarrow\left\{{}\begin{matrix}-2x-6< 0\\-2x-6\ne0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x>-3\\x\ne-3\end{matrix}\right.\)
\(5-\left|3x-1\right|=3\)
\(\left|3x-1\right|=2\)
\(\Rightarrow\orbr{\begin{cases}3x-1=2\\3x-1=-2\end{cases}}\Rightarrow\orbr{\begin{cases}3x=3\\3x=-1\end{cases}}\Rightarrow\orbr{\begin{cases}x=1\\x=\frac{-1}{3}\end{cases}}\)
vậy \(\orbr{\begin{cases}x=1\\x=\frac{-1}{3}\end{cases}}\)
\(\left|x+\frac{3}{4}\right|-5=-2\)
\(\left|x+\frac{3}{4}\right|=3\)
\(\Rightarrow\orbr{\begin{cases}x+\frac{3}{4}=3\\x+\frac{3}{4}=-3\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{9}{4}\\x=-\frac{15}{4}\end{cases}}\)
\(\left(1-2x\right)^2=9\)
\(\left(1-2x\right)^2=3^2\)
\(\Rightarrow1-2x=3\)
\(\Rightarrow2x=-2\)
\(\Rightarrow x=-1\)
vậy \(x=-1\)
\(\left(x+5\right)^3=-64\)
\(\left(x+5\right)^3=\left(-4\right)^3\)
\(\Rightarrow x+5=-4\)
\(\Rightarrow x=-9\)
vậy \(x=-9\)
\(\left(2x+1\right)^2=\frac{4}{9}\)
\(\left(2x+1\right)^2=\left(\frac{2}{3}\right)^2\)
\(\Rightarrow2x+1=\frac{2}{3}\)
\(\Rightarrow2x=\frac{-1}{3}\)
\(\Rightarrow x=\frac{-1}{6}\)
vậy \(x=-\frac{1}{6}\)
a) 2(x-1)2 - 4(x+3)2 + 2x(x-5)
= 2(x2 -2x +1)- 4(x2 + 6x +9) + 2x2 -10x
= 2x2 - 4x + 2 -4x2 - 24x - 36 + 2x2 - 10x
= (2x2 + 2x2 - 4x2) - (4x + 24x+10x) +(2-36)
= -38x-34
b) 2(2x+5)2 -3(4x+1)(1-4x)
= 2(4x2 + 20x + 25) + 3(4x+1)(4x-1)
= 8x2 +40x + 50 + 3(16x2 -1)
= 8x2 + 40x + 50 + 48x2 - 3
=56x2 +40x + 47
a, \(2\left(x-1\right)^2-4\left(x+3\right)^2+2x\left(x-5\right)\)
\(=2\left(x^2-2x+1\right)-4\left(x^2+6x+9\right)+2x\left(x-5\right)\)
\(=2x^2-4x+2-4x^2-24x-36+2x^2-10=-28x-44\)
b, \(2\left(2x+5\right)^2-3\left(4x+1\right)\left(1-4x\right)\)
\(=2\left(4x^2+20x+25\right)-3\left(1-16x^2\right)\)
\(=8x^2+40x+50-3+48x^2=56x^2+40x+47\)
a: P(x)=2x^5-2x^5+4x^4-3x^4+5=x^4+5
Q(x)=-5x^4+2x^4-x^3+3x^2-10x+2
=-3x^4-x^3+3x^2-10x+2
b: P(x)+Q(x)
=x^4+5-3x^4-x^3+3x^2-10x+2
=-2x^4-x^3+3x^2-10x+7
Q(x)-P(x)
=-3x^4-x^3+3x^2-10x+2-x^4-5
=-4x^4-x^3+3x^2-10x-3
P(x)-Q(x)=-(Q(x)-P(x))
=4x^4+x^3-3x^2+10x+3
1: =>(x+2018)(6x-3)=0
=>x+2018=0 hoặc 6x-3=0
=>x=1/2 hoặc x=-2018
2: x(x-11)+3(11-x)=0
=>(x-11)(x-3)=0
=>x=11 hoặc x=3
4: =>(x+5)(2x-4)=0
=>2x-4=0 hoặc x+5=0
=>x=2 hoặc x=-5
3: =>(x-3)(x+2)=0
=>x=3 hoặc x=-2
Bài 1:
\(6x\left(x+2018\right)-3\left(x+2018\right)=0\)
\(\Leftrightarrow\left(x+2018\right)\left(6x-3\right)=0\)
\(\Leftrightarrow3\left(x+2018\right)\left(2x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-2018\\2x=1\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-2018\\x=\dfrac{1}{2}\end{matrix}\right.\)
Bài 2:
\(x\left(x-11\right)+3\left(11-x\right)=0\)
\(\Leftrightarrow x\left(x-11\right)-3\left(x-11\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left(x-11\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=11\end{matrix}\right.\)
Câu 3:
\(x\left(x-3\right)-2\left(3-x\right)=0\)
\(\Leftrightarrow x\left(x-3\right)+2\left(x-3\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left(x+2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-2\end{matrix}\right.\)
Câu 4:
\(2x\left(x+5\right)-4\left(x+5\right)=0\)
\(\Leftrightarrow\left(x+5\right)\left(2x-4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-5\\2x=4\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-5\\x=2\end{matrix}\right.\)
=>0,2x+0,4-0,5x=0,25-0,5x+0,25
=>0,2x+0,4=0,5
=>0,2x=0,1
=>x=1/2
x=(-2-sqrt(164))/-10=(1+sqrt(41))/5=1.481
x=(-2+sqrt(164))/-10=(1-sqrt(41))/5=-1.081
kích cho minh nha